2013 IEEE 77th Vehicular Technology Conference (VTC Spring) 2013
DOI: 10.1109/vtcspring.2013.6692626
|View full text |Cite
|
Sign up to set email alerts
|

LTE UE Energy Saving by Applying Carrier Aggregation in a HetNet Scenario

Abstract: Abstract-In this work it is examined if downlink CarrierAggregation (CA) can be used to save UE energy. A dual-receiver LTE release 10 UE is compared with a single-receiver LTE release 8 UE. The models are based on scaling of an existing LTE release 8 UE power model. The energy consumption of the UEs is examined in a Heterogeneous Network scenario consisting of macro and small cells. The unexpected conclusion is that CA UEs can save energy, compared to LTE release 8 UEs, if they, depending on cell load, experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…However, the higher throughput makes the download time shorter, allowing the device to go to the sleep state soon after the download has been finished. In [43,44], it is indicated that average UE power consumption with two frequency carrier aggregation does not exceed that with single frequency carrier. Furthermore, a 99.7% reduction of UE power consumption could be achieved via a combination of traffic offloading and dynamic on/off [45].…”
Section: Mmwave-integrated Cellular Networkmentioning
confidence: 99%
“…However, the higher throughput makes the download time shorter, allowing the device to go to the sleep state soon after the download has been finished. In [43,44], it is indicated that average UE power consumption with two frequency carrier aggregation does not exceed that with single frequency carrier. Furthermore, a 99.7% reduction of UE power consumption could be achieved via a combination of traffic offloading and dynamic on/off [45].…”
Section: Mmwave-integrated Cellular Networkmentioning
confidence: 99%
“…6: l = l + 1. 7: Update the dual variables δ, ϑ, γ, θ, and ρ according to (24) to (28). 8: if σ l+1 − σ l < △ ′ , ∀σ ∈ {δ, ϑ, γ, θ, ρ} 9: convergence=true.…”
Section: Algorithmmentioning
confidence: 99%
“…Upon these facts, numerous CA techniques have been developed for throughput improvement [20]- [23]. However, CA may also increase the energy consumption for both base stations and users if not appropriately utilized [24]. Recently, a dynamic CA scheduling algorithm has been developed in [25] to improve the EE of uplink transmission.…”
Section: Introductionmentioning
confidence: 99%
“…To estimate what can be expected from the measurements the power model from [6] is applied to scenario B presented above. In this scenario the UE is receiving a 1 GB file via FTP.…”
Section: E Theoretical Current Consumption Estimationmentioning
confidence: 99%
“…Since then researchers have estimated the current consumption of CA UEs by extending empirical models based on measurements on LTE release 8 UEs. In [6] DL CA current consumption was studied by increasing the bandwidth and number of RF chains of a previously established single-chain model, while [7] presented a similar study for uplink (UL) CA by combining measurements on multiple release 8 power amplifiers. Both studies showed that if CA provides a significant throughput increase then energy can be saved, but until now the conclusions have not been validated by real measurements.…”
mentioning
confidence: 99%